Biochar Age and Crop Rotation Impacts on Soil Quality. Issue 5 (28th September 2017) - Aller, Deborah; Mazur, Ross; Moore, Kenneth; Hintz, Roger; Laird, David; Horton, Robert
Abstract : Core Ideas: Crop rotations including switchgrass were found to build soil organic C and N Biochar amendments increased soil C and N, pH, and gravity drained water content Total soil C and N increases with biochar age suggest negative priming Biochar and switchgrass offset negative effects of biomass harvesting on soil quality Corn residue removed from Midwestern farms is a large potential source of biomass for cellulosic bioenergy production in the US long‐term harvesting of biomass, however, may lead to the degradation of soil quality unless management practices that compensate for the removal of biomass are used. In this study, biochar amendments and long‐term crop rotations that include triticale and switchgrass with corn and soybeans were hypothesized to reduce the negative effects of biomass harvesting on soil quality. Chemical breakthrough curves, measured for intact soil cores indicate that crop rotations that include switchgrass or triticale increased both retardation and dispersivity relative to conventional rotations and biochar amendments decreased dispersivity relative to controls. Across all crop rotations, there was an increase in total soil C and N, soil C/N ratio, pH and gravity drained water content, and a decrease in bulk density for soils treated with biochar relative to no‐biochar controls. No significant effect of biochar age on soil physical properties was measured in 2014 but significant increases with biochar age were found for total soil C and N in 2016, suggesting a synergistic interaction (negative priming). Continuous switchgrass stands were found to build soil organic C and N, increase retention of plant available P and K, and lower bulk density relative to the continuous corn cropping system. The results suggested that soil biochar amendments and crop rotations that included switchgrass helped mitigate some of the adverse effects of biomass harvesting on soil quality.